2016
DOI: 10.1177/1526602816680570
|View full text |Cite|
|
Sign up to set email alerts
|

First-in-Human Experience With the Gore Balloon-Expandable Covered Endoprosthesis in Iliac Artery Occlusive Disease

Abstract: This positive first-in-human experience with the Gore balloon-expandable covered endoprosthesis suggests this device will have an important role in the management of aortoiliac occlusive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Iliac artery stenting has been largely successful, with good results over long-term follow-up, 24 particularly when stentgrafts have been used. 25 A recent first-in-human evaluation of the VBX Stent Graft reported a positive experience, 26 corroborated by the current study with 100% technical success, 97% acute procedure success, and a TLR rate of 2.3% at 9 months. Unlike other iliac stenting trials supporting FDA approval, this study was designed to reflect current practice.…”
Section: Discussionsupporting
confidence: 81%
“…Iliac artery stenting has been largely successful, with good results over long-term follow-up, 24 particularly when stentgrafts have been used. 25 A recent first-in-human evaluation of the VBX Stent Graft reported a positive experience, 26 corroborated by the current study with 100% technical success, 97% acute procedure success, and a TLR rate of 2.3% at 9 months. Unlike other iliac stenting trials supporting FDA approval, this study was designed to reflect current practice.…”
Section: Discussionsupporting
confidence: 81%
“…The most significant ABI improvement was reported by Bosiers et al, 26 with a mean ABI measurement of 0.59 at Journal of Vascular Surgery baseline, 0.98 immediately after stenting, and 0.99 at 12 months. The smallest ABI improvement was reported by Holden et al, 32 with mean ABI measurements of 0.79 at baseline and 0.95 at 12 months. Table VI.…”
Section: Resultsmentioning
confidence: 75%
“…All but one patient completed the 12-month follow-up in study reported by Holden et al 32 (no mean follow-up provided); similarly, Deloose et al 27 reported outcomes through 12 months (no further follow-up statistics provided). c All patients completed the 6-month follow-up in this study (no mean follow-up provided).…”
Section: Comparison Of Devices a Comparison Of The Results Of Each Cmentioning
confidence: 90%
See 2 more Smart Citations